Psychometric properties of the portuguese version of the pain self-efficacy questionnaire. - Ferreira-Valente, M. Alexandra (2016)
Aims: This study sought to translate and evaluate the psychometric properties of a European Portuguese version of the Pain Self-Efficacy Questionnaire (P-PSEQ), in order to enable its use in clinical and cross-cultural studies. Material and Methods: The Pain Self-Efficacy Questionnaire was translated into European Portuguese and then back-translated into English. A consensus version of the translated version was pre-tested with a pilot sample, followed by cognitive debriefing, resulting in a final version of the measure. A convenience sample of 174 Portuguese adults with chronic musculoskeletal pain completed the Portuguese Pain Self-Efficacy Questionnaire (P-PSEQ) and criterion measures of pain intensity (Numerical Ratings Scale), pain interference (Portuguese Brief Pain Inventory Interference Scale), quality of life and general health (SF-12), and psychological functioning (Hospital Anxiety and Depression Scale). Cronbach’s alpha and composite reliability coefficients were computed as measures of reliability, and confirmatory factor analysis was performed. Pearson correlation coefficients between the P-PSEQ score and the criterion measures were computed to evaluate the construct validity of the scale. Results: The P-PSEQ demonstrated good to excellent reliability (Cronbach’s alpha = 0.88 and Composite reliability = 0.92), and showed moderately strong associations with the criterion measures in the hypothesized directions, supporting its cons - truct validity. Additionally, the confirmatory factor analysis supported a single factor solution, as hypothesized. Conclusions: The findings provide strong support for the reliability and validity of the P-PSEQ. Research is needed to determine the responsivity of the P-PSEQ and to establish the generalizability of the results in other samples of Portuguese patients with chronic pain.